(untitled) (Doctor Virtualis, 2023)
The paper deals with the problem of predicative analogical connections in the Aristotelian theory of demonstration, where they are marginal, and with its developments in the thirteenth-century medieval latin exegetical tradition. Grosseteste claims that demonstration can prove predicates that are said analogically of different subjects; Kilwardby and, after him, even more Giles of Rome show that this aim can be reached also through a medium analogically connected to the extreme terms. Giles upholds in a passage the existence of a hierarchical order among properties analogically demonstrated; somewhere else, however, he shows that they can configure more variously. In the following century, John Buridan resumes the basic lines of those interpretations, in the framework of a general widening of the features of Aristotelian science; maybe, his ideas on analogy could represent an initial stage of this tendence.